El barrio San Francisquito : una mirada construida participativamente. María Elena Aradas Diaz-coord. Graciela Enria, Melina Dachesky y Carlos C. Fernández. CEFEDER: Rosario, 2017 - Suárez, Ana Lourdes (2018)
Fil: Suárez, Ana Lourdes. Universidad Católica Argentina; Argentina